Non-domestic hot water heating systems - Teekaram, Arnold (Chartered Institute of Building Services Engineers, 2010)
The Chartered Institution of Building Services Engineers (CIBSE) has published AM14: Non-domestic hot water heating systems, a comprehensive application manual that describes a logical sequence of processes to help engineers design efficient heating systems. The newly released publication, covering water-based heating systems for buildings other than dwellings with a total installed capacity from 45kW up to 2MW, is expected to receive a warm welcome from the building services community as the last CIBSE guide on the subject was published more than 20 years ago.